THE DIVERSITY OF REPTILES ON SEVERAL HABITAT TYPES IN CAMPUS AREA OF SRIWIJAYA UNIVERSITY INDRALAYA, OGAN ILIR - Saptalisa, Wenny; Yustian, Indra; Setiawan, Arum (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2015)
The Diversity of Reptiles on Several Habitat TypesÂ in Campus Area of Sriwijaya University Indralaya, Ogan Ilir was aimed to determine the diversity of amphibian species present in this area. The research has been done in March until May 2015, in the campus of the Sriwijaya University, Indralaya. The method in this study is use the transect method by placing seventh transect line on line with the direction of cutting contour lines. Data collection techniques using the Visual Encounter Survey (VES) and Pit-Fall Trap method in combination with the Straight Line Method and Fence (Drift Fence). Results from this study recorded 11 species of amphibians from five families of the Anura Order. Average diversity index at Sriwijaya University Indralaya region is 1.70 which fall into the medium category.Â Keywords : Sriwijaya university, amphibians, transect,diversity